2019
DOI: 10.1111/acer.14189
|View full text |Cite|
|
Sign up to set email alerts
|

Technology‐Delivered Cognitive‐Behavioral Interventions for Alcohol Use: A Meta‐Analysis

Abstract: Background: Cognitive-behavioral therapy (CBT) has long-standing evidence for efficacy in the treatment of alcohol use, yet implementation in clinical practice has been challenging. Delivery of CBT through technology-based platforms, such as web-based programs and mobile applications, has the potential to provide widespread access to this evidence-based intervention. While there have been reviews indicating the efficacy of technology-based delivery of CBT for various psychiatric conditions, none have focused o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
2
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 72 publications
0
41
2
3
Order By: Relevance
“…They show promise to increase participant access, engagement, and outcomes; to improve reach and cost-effectiveness; and ultimately to provide a viable AUD treatment option for individuals in a variety of populations. 75 , 76 An emerging body of literature is examining technology-based, e-health, or mobile interventions for couples with AUD. Findings from the limited emerging literature on technology-based couple interventions are encouraging.…”
Section: Future Directions For Researchmentioning
confidence: 99%
“…They show promise to increase participant access, engagement, and outcomes; to improve reach and cost-effectiveness; and ultimately to provide a viable AUD treatment option for individuals in a variety of populations. 75 , 76 An emerging body of literature is examining technology-based, e-health, or mobile interventions for couples with AUD. Findings from the limited emerging literature on technology-based couple interventions are encouraging.…”
Section: Future Directions For Researchmentioning
confidence: 99%
“…Others responded positively because the messages served as a reminder to not drink or were positvely reinforcing when patients were able to enter zeros. Given the large interest in technology-based care for alcohol and other substance use 53 , 54 and in particular text-messaging interventions, 55 further studies should examine patient experience and implementation of such technology in primary care and other healthcare settings. Similarly, not all patients felt that the therapy component was helpful for them or what they were expecting.…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al [53] concluded that computerized cognitive therapy helps cognitive impairment and impulse control of patients with substance use disorder and invited them to continue with this research line for the understanding of the underlying brain mechanisms of cognitive therapy. Finally, Kiluk et al [54], through a review of the literature, found results that show benefits in interventions based on Cognitive Behavioral Therapy developed through technology with chronic alcohol consumers.…”
Section: Neuropsychological Rehabilitation For Addictionsmentioning
confidence: 99%